Determination of Real-Time Flood Distribution using Flood Meter - Irwan, Fahmi Idris; Emay Shah, Mohamad Shafiq; Syed Zaheruddin, Syed Danial; Abdul Kadir, Muhammad Azraie (Multidisciplinary Applied Research and Innovation, 2024)
There are many negative effects of flood disasters, including loss of life, an increase in fatalities, and even damage to the economy. The attack has caused damage to many infrastructures and deaths among many people. In Batu Pahat, Johor, there was an unexpected flood that hit the Taman Universiti community on the March 2023. Flood meter apps were evaluated for their ability to detect flood so that residents living near flood zones in Taman Universiti would be aware of flooding conditions. Using a flood meter, this study were able to pinpoint the location affected by the flood and predict the rising depth of the river.